REDOX DEPOSITION OF MnO 2 NANOPARTICLES ON RICE HUSK BASED ACTIVATED CARBON AS HIGH-PERFORMANCE ELECTRODE MATERIAL FOR PSEUDO-CAPACITORS - Abdul Hayat Kasim; Muhammad Zakir; L. Musa Ramang; Bannu Abdussamad (Jurnal Akta Kimia Indonesia (Indonesia Chimica Acta), 2017)
MnO2/rice husk activated carbon (KASP) nanocomposites have been synthesized by directly reducing KMnO4 with KASP in an aqueous solution. XRD diffraction data showed a broad and typical peak MnO2 at 37 2theta as an indicator that the compound obtained are amorphous. Fluorescence data (XRF) also supports that after addition of KMnO4 to the rice husk based acticated carbon solution concurrently MnO2 nanoparticles deposition takes place on the surface of KASP. It is found that the morphologies of MnO2 grown on KASP can be tailored by varying the reaction ratio of KASP and KMnO4. A pseudo-capacitor with high energy density was fabricated by using MnO2/RHAC nanocomposite as positive electrode and activated carbon as negative electrode in 1 M Na2SO4 aqueous electrolyte. The pseudocapacitor can be cycled reversibly in the cell voltage of 0.2 V, and delivers a specific capacitance of 25.4 mF g-1 (based on the total mass of active electrode materials of 9.4 mg), which is much higher than that of supercapacitor without MnO2 deposition (8.6 F g-1), or there is significance increase in capacitance (± 3000 times). We obtained also that supercapacitor’s electrode developed from rice husk based activated carbon has a better performance compared to one developed from commercially activated carbon material. Such a better electrochemical performance makes nanocomposite of MnO2/KASP as a promising electrode material for supercapacitors.